Minab school bombing: what evidence is there that the US was responsible? - McClure, Tess (The Guardian, 2026)
Trump has blamed Iran for the mass killing at Shajareh Tayyebeh primary school but geolocation, videos, satellite imagery and fragments apparently recovered from the site indicate otherwise.
Keywords: Donald Trump; Human rights; International law; Iran; Law; Middle East and north Africa; US news; US-Israel war on Iran; World news